FEATURES IN REGIONAL DEVELOPMENT AND TOURIST POTENTIAL OF THE MOUNTAIN REGIONS AND AREAS IN BULGARIA - Kamen Dimitrov PETROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The focus on mountain areas within the European Union in recent years has become an essential part of the common regional policy, which is aimed at making spatial development a top priority of the European institutions. In the present exhibition an analysis is made of the tourist potential of the mountain municipalities in Bulgaria, which develop tourism. The territorial peculiarities of these regions are presented, their peculiarities and specifics in the context of their regional development are considered. The opportunities for them to improve their tourism potential and, above all, to create a new environment for implementing regional development policies are also outlined. The relevant conclusions and recommendations for achieving a sustainable tourist framework of the mountainous regions in Bulgaria have been made.